Pengaruh Pad Dalam Mendukung Kemandirian Fiskal Jawa Tengah Untuk Mendukung Pertumbuhan Ekonomi - Boby Septika Tri Wibowo (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
In the context of regional autonomy, fiscal capacity plays a crucial role in supporting sustainable regional development and economic growth. This study aims to analyze the role of Local Own-Source Revenue (Pendapatan Asli Daerah/PAD) in strengthening fiscal independence and its implications for economic growth in Central Java Province. This research employs a quantitative approach with an explanatory design. Secondary data were obtained from regional budget realization reports and Gross Regional Domestic Product (GRDP) statistics of Central Java Province for the period 2019–2024. Data were analyzed using simple linear regression techniques. The results indicate that Local Own-Source Revenue has a positive and significant effect on fiscal independence, with a regression coefficient of 1.52 and a significance level of 0.014, explaining 57.6 percent of the variation in fiscal independence. Furthermore, fiscal independence also has a positive and significant impact on economic growth, as indicated by a regression coefficient of 1.52 and a significance value of 0.014. These findings confirm that optimizing local revenue sources is essential for strengthening fiscal independence and enhancing sustainable regional economic growth.